Examining the potential contribution of social theory to developing and supporting Australian Indigenous-mainstream health service partnerships - Haynes, E.; Taylor, Kate; Durey, Angela; Bessarab, Dawn; Thompson, S. (BioMed Central Ltd., 2014)
Introduction: The substantial gap in life expectancy between Indigenous and non-Indigenous Australians has been slow to improve, despite increased dedicated funding. Partnerships between Australian Indigenous and mainstream Western biomedical organisations are recognised as crucial to improved Indigenous health outcomes. However, these partnerships often experience challenges, particularly in the context of Australia’s race and political relations. Methods: We examined the relevant literature in order to identify the potential role for social theory and theoretical models in developing and maintaining intercultural partnerships. Having identified relevant theoretical models, terms and possible key words, a range of databases were searched and relevant articles selected for inclusion. An integrative approach brought together theoretical models and practical considerations about working in partnership, to inform our analysis of the literature. Findings: Considering partnerships between Australian Indigenous and mainstream health organisations as 'bi-cultural' is simplistic: rather they are culturally diverse across social and professional levels. As such, partnerships between Australian Indigenous and mainstream health organisations may be better conceptualised as 'intercultural', operating across diverse and shifting cultural frames of reference. Theories identified by this review as useful to guide partnerships include power relations, reflexivity and dialogue, borders and strangeness and the intercultural or third space. This paper examines how these theoretical approaches can develop understanding and improve intercultural engagement between mainstream and Australian Indigenous partners in healthcare.Conclusions: Rather than viewing partnerships merely as arrangements between disembodied entities, sometimes contractual in nature, they are better seen as activities between people and organisations and essentially dependent on relationships, occurring in an intercultural space that is complex, dynamic and subject to changes in power relations. Theoretical models aiming to understand and improve partnerships indicate the complexity of building and maintaining such partnerships and stress the importance of understanding factors that can strengthen or derail their effectiveness. While the theories presented here are by no means exhaustive, they nonetheless provide a series of entry points through which to engage with the issue and expand the discourse. This approach allows the transformative nature of Australian Indigenous-mainstream 'culture' to be explored and understood in its lived expression; rather than relegated to prescriptive categories.